Henry James Goes to Paris - Brooks, Peter, 1938- (Book collections on Project MUSE., 2007)
'Henry James Goes to Paris' tells the story of the year the young novelist - aged 32 - spent in Paris, in 1875-76. He traveled to Paris with the intention of a much longer, perhaps a life-long stay, but eventually settled in London.